Attention-deficit/hyperactivity disorder is associated with reduced levels of serum low-density lipoprotein cholesterol in adolescents. Data from the population-based German KiGGS study. (3rd July 2019) - Pinho, Raquel; Wang, Biyao; Becker, Andreas; Rothenberger, Aribert; Outeiro, Tiago F.; Herrmann-Lingen, Christoph; Meyer, Thomas
Abstract: Objectives: Attention-deficit/hyperactivity disorder (ADHD) is a multifactorial, complex and the most common neurodevelopmental disorder in childhood. In this analysis, we tested the hypothesis that altered serum lipid patterns are associated with ADHD. Methods: Using data from the nationwide, population-based German Health Interview and Examination Survey for Children and Adolescents (KiGGS), we compared serum levels of total cholesterol, high-density (HDL) and low-density lipoprotein (LDL) cholesterol, and also triglycerides, in participants with physician-diagnosed and/or suspected ADHD, as defined by a value of ≥7 on the hyperactivity-inattention subscale of the Strengths and Difficulties Questionnaire (SDQ), with non-ADHD controls. Results: Among 6, 898 participants aged between 11 and 17 years, 666 (9.7%) had a physician-based diagnosis of ADHD and/or suspected ADHD. We found correlations between the parent-rated SDQ scores on the hyperactivity-inattention subscale and concentrations of triglycerides ( r  = 0.064, p  < .001), total cholesterol ( r  = −0.026, p  = .033), HDL cholesterol ( r  = −0.059, p  < .001) and LDL cholesterol ( r  = −0.027, p  = .031). In multivariate models, low serum levels of LDL cholesterol remained a significant predictor of ADHD (Exp(β) = 0.382, 95% confidence interval = 0.165−0.888, p  = .025). Conclusions: Our findings in a large, nationwide and representative sample of German adolescents demonstrated a small, but significant and inverse link between LDL cholesterol levels and symptoms of ADHD. Further studies are required to decipher the biochemical mechanisms behind this relationship.